Self analysis - "Horney, Karen" (New York, 1994)
This book discusses the driving forces in the neuroses, the different stages of psychoanalytic understanding, the patient's and the analyst's share in the psychoanalytic process, occasional and systematic self-analysis, and the realistic expectations of undertaking self-analysis.
Keywords: Psycho analysis